NUTRITIONAL INTERVENTION FOR ENHANCING THE REPRODUCTIVE PERFORMANCE OF CROSSBRED PIGS - GOPINATHAN, A; KARTHICKEYAN, S M K; RAMESH, J; SIVASELVAM, S N (The Indian Journal of Animal Reproduction, 2023)
The study was carried out to assess the effect of nutritional intervention in the feeding regimen of crossbredpigs (N=21) on the reproductive performances such as litter size at birth and at weaning, litter weight at birth andat weaning, birth and weaning weight and pre-weaning mortality. Twenty one crossbred sows aged more than oneyear and farrowed once, were taken for the .study in Pig Breeding Unit functioning at Livestock Research Station,Kattuapkkam. The standard feeding protocol was designed taking into consideration of dewormers, vitamins andminerals mixture and calcium supplementation along with normal concentrate feeding. The results showed highlysignificant differences (P
Keywords: Litter traits; Reproductive performance; Nutritional supplementation